2019
DOI: 10.1177/1933719119828096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sperm DNA Fragmentation via Halosperm Technique and TUNEL Assay Before and After Cryopreservation

Abstract: Aim: Human sperm DNA fragmentation is one of the factors suggested for male infertility. The ratio of sperm DNA damage in semen may adversely affect both the fertilization rate and the embryo development of in vitro fertilization/ intracytoplasmic sperm injection cycles. Sperm cryopreservation both increases the success rates in assisted reproductive techniques (ARTs) and contributes to the preservation of fertility before testis surgery, chemotherapy, and radiotherapy. The aim of the current study is to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
4
14
0
2
Order By: Relevance
“…Despite the extensive progress that has been made in the field, decreases in sperm motility and DNA integrity are commonly observed after cryopreservation 30,39 . In this report we found that rapid freezing using R18S3 + MTG also significantly reduced sperm motility and increased DNA fragmentation in both wildtype and mutant mouse strains, observations consistent with previous results in mice 26,29 and humans [30][31][32]40 . In this report, we also found that DFI of frozen-thawed sperm from mutant mouse strains was consistently and highly correlated with male mouse fertility compared to traditional measures of sperm quality (count, morphology, and motility).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite the extensive progress that has been made in the field, decreases in sperm motility and DNA integrity are commonly observed after cryopreservation 30,39 . In this report we found that rapid freezing using R18S3 + MTG also significantly reduced sperm motility and increased DNA fragmentation in both wildtype and mutant mouse strains, observations consistent with previous results in mice 26,29 and humans [30][31][32]40 . In this report, we also found that DFI of frozen-thawed sperm from mutant mouse strains was consistently and highly correlated with male mouse fertility compared to traditional measures of sperm quality (count, morphology, and motility).…”
Section: Discussionsupporting
confidence: 92%
“…Sperm DNA integrity is essential for embryo development [25][26][27] , although sperm with minimal DNA damage retain fertilizing ability 28 . Limited studies in animals and humans have shown that sperm DNA can be damaged by cryopreservation 26,[29][30][31][32] , and there is a growing concern about the impact of cryodamage on ART outcome. Thus, the objectives of the present study were to study (1) the effects of cryopreservation on sperm DNA integrity, (2) the correlation between post-thaw sperm DNA fragmentation index (DFI) as a measure of sperm DNA fragmentation and conventional sperm parameters (count, motility and morphology), and (3) the relationship between post-thaw sperm DFI and fertility in mice.…”
mentioning
confidence: 99%
“…Freezing and thawing exert detrimental effects on spermatozoa that lead to poor motility (3,16,28). Whilst there is no agreement in the literature on whether cryopreservation induces DNA damage, a number of studies reported DNA fragmentation in post-thaw spermatozoa (11)(12)(13). Post-cryopreservation analysis revealed the link between the production of ROS following the changes of mitochondrial membrane properties and loss of motility and increased DNA fragmentation in frozen-thawed sperm (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined cryodamage in spermatozoa and indicated oxidative stress as one of the main causes of alterations in function due to an imbalance between reactive oxygen species (ROS) and the antioxidant system of spermatozoa (10). Although the effect of cryopreservation on sperm DNA integrity is controversial, many studies propose that cryopreservation induces DNA fragmentation (11)(12)(13). Production of ROS has been suggested to be mainly responsible for DNA damage in post-thaw spermatozoa (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…After cleaning with PBS, 30 μL of TUNEL reaction reagent (Roche, USA) was placed to each sample, they were incubated for 1 hour at 38°C in a humid dark box. Next, after rinsing sufficiently with PBS and examination with fluorescence microscope under 100× magnification (33,34), the nuclei of sperm cells with fragmented DNA (TUNEL+) indicated bright green color, while the nuclei of the normal cells (TUNEL-) presented pale green color.…”
Section: Assessment Of Sperm Apoptosis By Tunel Assaymentioning
confidence: 99%